Potential of caffeic acid as an effective natural antioxidant for polypropylene-polyethylene copolymers: A DFT and experimental study (2024)
Caffeic acid (CAF) i is a polyphenolic compound commonly found in plants, valued for its ability to act as an antioxidant. This study focused on investigating the impact of a natural antioxidant, specifically caffeic acid (CAF), compared to two synthetic antioxidants, butylated hydroxyanisole (BHA) and butylated hydroxytoluene (BHT), on the thermal stability of propylene/ethylene copolymer (C-PP/PE), Aiming to establish a theoretical framework for the advancement of novel polymeric antioxidant compounds. Theoretical calculations were conducted to determine each compound's thermodynamic properties and antioxidant activity. The phenolic hydroxyl bond dissociation enthalpy (BDE) values revealed that BHA had the lowest value (325.6 kJ mol−1), trailed by CAF (328.2 kJ mol−1) and BHT (341.3 kJ mol−1), indicating a higher electron-donating capacity of BHA. Transition energy (TS) calculations indicated that BHA had the lowest TS energy (49.29 kJ mol−1), succeeded by CAF (57.61 kJ mol−1) and then BHT (75.57 kJ mol−1), suggesting greater efficiency in radical scavenging. Additionally, the obtained rate constants showed that CAF had the highest hydrogen abstraction rate (k = 1.05 × 10⁵ M⁻1 s⁻1), followed by BHA (k = 1.17 × 10⁴ M⁻1 s⁻1), and then BHT (k = 4.2 × 10³ M⁻1 s⁻1). These results support the effectiveness of CAF as a potentially more active antioxidant. In the experimental part of this study, it was observed that C-PP/PE with BHA showed a lower melt flow index (MFI) (8.51), indicating more excellent thermal stability. On the other hand, samples containing natural caffeic acid extracts exhibited a gradual decrease in MFI with increasing CAF concentration (MFI of 9.4, 8.82, 7.59, 6.44, and 5.98 for concentrations of 0.025, 0.05, 0.075, 0.1, and 0.125 ppm, respectively), suggesting a progressive improvement in the thermal stability of C-PP/PE with increasing natural antioxidant. In TGA analyses, decomposition was observed around 340 °C in samples without additives and those containing 0.1 ppm of BHA. In contrast, samples with different concentrations of CAF showed delayed degradation, observed in the temperature range of 380–400 °C. This delay in degradation indicates that CAF imparts more excellent thermal stability to C-PP/PE copolymer, as it reaches temperatures above 400 °C before starting its decomposition. These findings support the feasibility of using natural antioxidants such as CAF to improve the thermal properties of copolymers.